Underworld rise of the Lycans - Rosenberg, Tom; Tatopoulos, Patrick; Sketch Films (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
Traces the origins of the centuries-old blood feud between the aristocratic vampires and their onetime slaves, the Lycans. In the Dark Ages, a young Lycan named Lucian emerges as a powerful leader who rallies the werewolves to rise up against Viktor, the cruel vampire king who has enslaved them. Lucian is joined by his secret lover, Sonja, in his battle against the Vampire army and his struggle for Lycan freedom
Special features: Filmmakers commentary: Underworld: Rise of the Lycans-- from script to screen ; the origin of the feud ; re-creating the Dark Ages ; The look of Underworld: Rise of the Lycans ; music video:'Deathclub (Wes Borland/Renholder Remix)' by William Control feat. Matt Skiba
Title from title screen
Story by Len Wiseman & Robert Orr and Danny McBride ; screenplay by Danny McBride and Dirk Blackman & Howard McCain ; director of photography, Ross Emery ; editors, Peter Amundson, Eric Potter ; music, Paul Haslinger
Cast: Michael Sheen, Bill Nighy, Rhona Mitra, Steven Mackintosh, Kevin Grevioux
DVD Format
English, dubbed French, dubbed Spanish or dubbed Thai dialogue, English, French, Korean, Mandarin, Spanish or Thai subtitles
Keywords: Vampires -- Drama; Werewolves -- Drama; Good and evil -- Drama